Joint Venture for Product Innovation and Cartel Stability under Vertical Differentiation - Luca Lambertini; Cristina Iori (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2000)
We describe a vertically dierentiated market where firms choose between activating either independent ventures leading to distinct product qualities, or a joint venture for a single quality. Then, firms either repeat the one-shot Nash equilibrium forever, or behave collusively, according to discount factors. We prove that there exists a parameter region where the joint venture makes it more difficult for firms to sustain collusive behaviour, as compared to independent ventures. Therefore, public policies towards R&D behaviour should be designed so as not to become inconsistent with the pro-competitive attitude characterising the current legislation on marketing practices.
Keywords: 330